2015
DOI: 10.1161/atvbaha.115.305597
|View full text |Cite|
|
Sign up to set email alerts
|

Local MicroRNA Modulation Using a Novel Anti-miR-21–Eluting Stent Effectively Prevents Experimental In-Stent Restenosis

Abstract: Objective Despite advances in stent technology for vascular interventions, in-stent restenosis (ISR) due to myointimal hyperplasia (MH) remains a major complication. Approach and Results We investigated the regulatory role of microRNAs in MH/ISR, utilizing a humanized animal model in which balloon-injured human internal mammary arteries (IMAs) with or without stenting were transplanted into RNU rats, followed by microRNA profiling. miR-21 was the only significantly up-regulated candidate. In addition, miR-21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 37 publications
3
98
0
Order By: Relevance
“…Local delivery of vascular therapeutic miRNA modulators via coated stents has recently been shown to be safe and highly effective. 44 Direct delivery of miR-210 attenuates cardiac injury in mice and has been suggested as a therapeutic agent in ischemic heart disease. 45 Results from our study indicate that not only hypoxia, but also other stimuli, including pathological shear stress and altered blood flow conditions, as well as conditions inducing apoptosis and dedifferentiation, can lead to miR-210 repression in the vasculature, resulting in a downstream induction of proapoptotic mechanisms mainly in SMCs.…”
Section: Eken Et Al Mir-210 Enhances Atherosclerotic Plaque Stabilitymentioning
confidence: 99%
“…Local delivery of vascular therapeutic miRNA modulators via coated stents has recently been shown to be safe and highly effective. 44 Direct delivery of miR-210 attenuates cardiac injury in mice and has been suggested as a therapeutic agent in ischemic heart disease. 45 Results from our study indicate that not only hypoxia, but also other stimuli, including pathological shear stress and altered blood flow conditions, as well as conditions inducing apoptosis and dedifferentiation, can lead to miR-210 repression in the vasculature, resulting in a downstream induction of proapoptotic mechanisms mainly in SMCs.…”
Section: Eken Et Al Mir-210 Enhances Atherosclerotic Plaque Stabilitymentioning
confidence: 99%
“…Also, a knock-down of miR-21 and miR-221 may reduce neointima formation after vessel injury [150]. Systemically administered antagomiRs and miRmimics have been the method of choice to explore their effect, but had substantial off-target effects and were primarily targeting the kidney, liver, lung and spleen with considerable side effects [150,151]. Therefore, the local administration of miRNAs as therapeutic agents in the prevention of ISR was evaluated [151].…”
Section: Mirna Therapeutics Via Drug Eluting Stentsmentioning
confidence: 99%
“…Systemically administered antagomiRs and miRmimics have been the method of choice to explore their effect, but had substantial off-target effects and were primarily targeting the kidney, liver, lung and spleen with considerable side effects [150,151]. Therefore, the local administration of miRNAs as therapeutic agents in the prevention of ISR was evaluated [151]. The authors successfully implanted antimiR-21 coated vascular stents into human left internal mammarian arteries, grafted those arteries into mice in abdominal aortal position and found a significantly reduced myointima formation compared with a control group treated with bare metal stents (BMS) [151].…”
Section: Mirna Therapeutics Via Drug Eluting Stentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach, Wang et al used an anti-21-coated stent to reduce ISR. 133 Alternative strategies for targeted delivery include conjugation to targeting molecules, such as antibodies, peptides, or other molecules, that allow achievement of site-specific delivery despite systemic administration. Using a different approach, Santulli et al, for example, showed that binding of endogenous miR-126-3p to the Ad-p27-126TS might prevent p27 overexpression in ECs but not in VSMCs.…”
Section: Site-specific Deliverymentioning
confidence: 99%